Use-case scenarios for an anti-Cryptosporidium therapeutic. - Paul G Ashigbie; Susan Shepherd; Kevin L Steiner; Beatrice Amadi; Natasha Aziz; Ujjini H Manjunatha; Jonathan M Spector; Thierry T Diagana; Paul Kelly (Public Library of Science (PLoS), 2021)
Cryptosporidium is a widely distributed enteric parasite that has an increasingly appreciated pathogenic role, particularly in pediatric diarrhea. While cryptosporidiosis has likely affected humanity for millennia, its recent "emergence" is largely the result of discoveries made through major epidemiologic studies in the past decade. There is no vaccine, and the only approved medicine, nitazoxanide, has been shown to have efficacy limitations in several patient groups known to be at elevated risk of disease. In order to help frontline health workers, policymakers, and other stakeholders translate our current understanding of cryptosporidiosis into actionable guidance to address the disease, we sought to assess salient issues relating to clinical management of cryptosporidiosis drawing from a review of the literature and our own field-based practice. This exercise is meant to help inform health system strategies for improving access to current treatments, to highlight recent achievements and outstanding knowledge and clinical practice gaps, and to help guide research activities for new anti-Cryptosporidium therapies.